Geophysical model of the mantle ore-forming system - D. Yosifov; R. Radichev (Геофизический журнал, 2019)
The paper deals with a generalized geophysical model of the mantle ore-forming system that covers three main parts: a) the area of origin of the ore substance; b) its transportation zone and c) the area of concentrated ore-formation ― a deposit. The essence of the model uses the modern achievements of metallogeny and deep geophysics on one hand, as well as original quantitative data on the structure of the astenosphere in the regions of large deposits of non-ferrous and metal ores deposits in Central Srednogorie and the Central Rhodopes on the other. As a result of geophysical studies longitudinal and transversal mantle faults have been tracked as well as the lifting of the heated roof of the asthenospheric layer. In addition quantitative data have been obtained on considerable vertical amplitudes of tectonic ruptures both on the Moho division of more than 7―14 km and on the upper boundary of asthenospheric layer where the amplitude is more than 60 km. The structure of endogenous ore-forming system described shows that two of its main parts, namely origination and localization of ore-bearing products are completely situated in asthenosphere and earth crust respectively. The third main part ― the transporting one occupies some restricted area of the upper mantle and the whole vertical size of the earth crust coincident with crust-mantle nods. The features of tectonosphere revealed within the limits of the mantle ore areas as well as specific geophysical character of asthenospheric layer certificate that within these areas favorable conditions were generated for emergence and functioning of convecting cells and ascending magmo-fluid flows. All the mentioned, stimulated origination of ore-bearing magma in asthenosphere layer and their movement to the surface, where in the Late Cretaceous (Srednogorie) and Paleogenic (Rhodopes) the mantle deposits were formed. The results of the studies conducted are the important step in clearing the problem of origination of the ore matter realized in asthenosphere.